Analytical Study of Indications of Writing Difficulties (Dysgraphia) and Efforts to Overcome Them in Students of SDN 02 Bantur, Malang, Indonesia - Moch. Ilman Fauzi (International Research and Development for Human Beings (IRDH), 2024)
Dysgraphia is a special difficulty where children cannot write or express their thoughts in writing because they cannot order or arrange words properly and coordinate their fine motor skills (hands) to write. The objectives of this study include knowing: 1) To find out the factors that cause children to experience indications of writing difficulties (Dysgraphia) in 5th elementary grades students of SDN 02 Bantur, Malang, 2) To find out the efforts made by teachers and parents to overcome indications of writing difficulties (Dysgraphia) of fifth-grade students of SDN 02 Bantur, Malang. The type of research is based on a qualitative approach with a case study research type. Data collection techniques are observation, interview, and documentation. Research results: 1) The implementation of learning activities in 5th elementary grades has been going well. the factors that cause writing difficulties (Dysgraphia) in students specifically the cause of dysgraphia are not known with certainty. Still, if dysgraphia occurs suddenly in children or people who have grown up then it is suspected that dysgraphia is caused by head trauma whether due to accidents, illness, and so on. 2) Efforts to overcome indications of writing difficulties (dysgraphia) in 5th elementary grades SDN 02 Bantur, namely, by providing additional tutoring and using various methods. 3) Barriers to overcoming indications of writing difficulties (dysgraphia) in grade V SDN 02 Bantur, namely, parents of students who experience indications of writing difficulties (dysgraphia) in 5th elementary grades pay less attention to the development of their children, motivation of students who experience indications of writing difficulties in 5th elementary grades to learn, practice and try is still lacking, and the impossibility of the school to monitor students one by one.